Impact of the biological definition of Alzheimer’s disease using amyloid, tau and neurodegeneration (ATN): what about the role of vascular changes, inflammation, Lewy body pathology? - Gauthier, S. (Transl Neurodegener, 2018)
BACKGROUND: The NIA-AA research framework proposes a biological definition of Alzheimer’s disease, where asymptomatic persons with amyloid deposition would be considered as having this disease prior to symptoms. DISCUSSION: Notwithstanding the fact that amyloid deposition in isolation is not associated with dementia, even the combined association of amyloid and tau pathology does not inevitably need to dementia over age 65. Other pathological factors may play a leading or an accelerating role in age-associated cognitive decline, including vascular small vessel disease, neuroinflammation and Lewy Body pathology. CONCLUSION: Research should aim at understanding the interaction between all these factors, rather than focusing on them individually. Hopefully this will lead to a personalized approach to the prevention of brain aging, based on individual biological, genetic and cognitive profiles.